PENGARUH ARUS KAS OPERASI DAN LABA BERSIH TERHADAP DIVIDEN KAS PADA PT SUMBER ALFARIA TRIJAYA TBK PERIODE 2014-2024 - Sindi Umadini Syafrina; Hendri Prasetyo (CV. Denasya Smart Publisher, 2025)
This study aims to determine the effect of Operating Cash Flow as measured by the Operating Cash Flow Ratio (OCF) and Net Profit with Net Profit Margin (NPM) on Cash Dividends using Dividend Per Share (DPS) at PT Sumber Alfaria Trijaya TBK. The research method used is an associative quantitative method. The population of this study is the financial statements of PT Sumber Alfaria Trijaya TBK, while the samples used are the financial position report, profit and loss report and cash flow report of PT Sumber Alfaria Trijaya TBK for the 2014-2024 period. The data analysis techniques used are descriptive statistical tests, classical assumption tests, multiple linear regression analysis tests, t tests, F tests and coefficients of determination processed using SPSS version 27. The results of the study indicate that partially Operating Cash Flow (Operating Cash Flow Ratio) does not have a significant effect on Cash Dividends (Dividend Per Share). While Net Profit Margin has a significant effect on Cash Dividends (Dividend Per Share), simultaneously Operating Cash Flow Ratio and Net Profit Margin have a significant effect on Cash Dividends (Dividend Per Share). With a determination coefficient of 54.0%.